Student Participation and Achievement in a Large Lecture Course With Game-Based Learning. (February 2016) - Nadolny, Larysa; Halabi, Andrea
Background The use ofgame-based learning strategies inhigher education has shown promise to increase studentmotivation andachievement . Although studies have begun to explore the structuring ofcourses as a game, little is known on who benefits the most from this type of instructional environment. Aim This research study explored theimpact of a large lecture course designed with game-based learning onparticipation andachievement .Game elements included narrative, quests, points, feedback, and badges. Method 71 undergraduate students participated in acase study utilizing amixed methods approach.Measures included course achievement, course participation, and a survey on beliefs and practices. Results Findings indicated students in a large course structured with game-based learning maintainedhigh participation and persistence inmeeting course requirements . In addition, overall achievement was not significantly correlated with age, gender, learning style, or game use, contradicting the research literature on game-based learning. Conclusions The use of game-based learning isbeneficial for engaging all students inlarge lecture courses, but more work is needed in determining which strategies are most effective for learning.